Cloud-based big data analytics in vehicular ad-hoc networks - Rao, Ram Shringar 1973-; Singh, Nanhay 1973-; Kaiwartya, Omprakash 1981-; Das, Sanjoy 1979- (IGI Global, 2020)
"This book covers a range of new concepts in emerging VANETs including the integration with cloud computing and big data analytics, emerging wireless networking concepts, and computing models"--